Sustained diffusion reversal with in-bore reperfusion in monkey stroke models: Confirmed by prospective magnetic resonance imaging. Issue 6 (June 2017) - Yi, Kyung Sik; Choi, Chi-Hoon; Lee, Sang-Rae; Lee, Hong Jun; Lee, Youngjeon; Jeong, Kang-Jin; Hwang, Jinwoo; Chang, Kyu-Tae; Cha, Sang-Hoon
Although early diffusion lesion reversal after recanalization treatment of acute ischaemic stroke has been observed in clinical settings, the reversibility of lesions observed by diffusion-weighted imaging remains controversial. Here, we present consistent observations of sustained diffusion lesion reversal after transient middle cerebral artery occlusion in a monkey stroke model. Seven rhesus macaques were subjected to endovascular transient middle cerebral artery occlusion with in-bore reperfusion confirmed by repeated prospective diffusion-weighted imaging. Early diffusion lesion reversal was defined as lesion reversal at 3 h after reperfusion. Sustained diffusion lesion reversal was defined as the difference between the ADC-derived pre-reperfusion maximal ischemic lesion volume (ADCD-P Match ) and the lesion on 4-week follow-up FLAIR magnetic resonance imaging. Diffusion lesions were spatiotemporally assessed using a 3-D voxel-based quantitative technique. The ADCD-P Match was 9.7 ± 6.0% (mean ± SD) and the final infarct was 1.2–6.0% of the volume of the ipsilateral hemisphere. Early diffusion lesion reversal and sustained diffusion lesion reversal were observed in all seven animals, and the calculated percentages compared with their ADCD-P Match ranged from 8.3 to 51.9% (mean ± SD, 26.9 ± 15.3%) and 41.7–77.8% (mean ± SD, 65.4 ± 12.2%), respectively. Substantial sustained diffusion lesion reversal and early reversal were observed in all animals in this monkey model of transient focal cerebral ischaemia.